MODERN TECHNOLOGIES AND SPECIAL EQUIPMENT FOR POTATO PRODUCTION - A. Yu. Izmaylov; N. N. Kolchin; Ya. P. Lobachevskiy; N. G. Kynev (Сельскохозяйственные машины и технологии, 2015)
Much attention at an exhibition was paid to potato planters and self-propelled and hook-on potato harvesters, working elements for soil lumps and stones separating, haulm extracting. Propulsion systems of combines increasing their flotation ability were shown also. Heavy-load trailers for potatoes transportation with devices for decrease in damage of tubers were presented among the other models. Lines for postharvest tubers processing with automatic control of potatoes giving increasing quality of work, provides decrease in expenses, were shown at the exhibition. There were the field plots with flat surface were organized for machines shown. Operation of harvest equipment was shown in sequence: harvesters - field vehicle - line of postharvest processing - transportation to the consumers in heavy-load vehicles.